ADOPTING 21ST CENTURY COMPETENCIES FOR A TECHNICAL UNIVERSITY CURRICULUM - Iurina, Maria; Gorlova, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Russian universities are involved in the global process of rethinking and remodelling of the higher educational system. They are expected to provide their students with a wide variety of skills, which are often referred to as "21st century competencies". Such skills as critical thinking, decision making, the ability to communicate effectively and solve problems through negotiation and collaboration are needed for success in study and careers. For the universities it means growing importance of making curriculum relevant, helping students learn how to teach themselves, and fostering creativity. This article explores the quality of learning in the Russian technical university and concludes that the current pedagogy has not adapted yet to address the challenges of the twenty-first century. The traditional approach, based upon a teacher-centred focus on rote learning still prevails.  Through this research it was found that there are different pedagogical approaches that could develop different 21st century competencies by technical students. The article concludes with a discussion around some innovative teaching methods that make lessons more student-driven and motivating.